2008
DOI: 10.1016/s1441-3523(08)70112-8
|View full text |Cite
|
Sign up to set email alerts
|

Development through Sport: Building Social Capital in Disadvantaged Communities

Abstract: Traditional delivery of sport development programs, especially at the community level, face particular challenges under neoliberal ideology. While several issues are evident, this paper addresses the issue of development through sport for disadvantaged communities. It reviews models where sport was employed to develop better community and citizen life outcomes and t o d e a l wi t h s o c i a l i s s u e s p r e v i o u s l y d e a l t wi t h t h r o u g h " we l f a r e s t a t e " p r o c e s s e s. These ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
149
1
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(179 citation statements)
references
References 31 publications
7
149
1
11
Order By: Relevance
“…For example, sports are often regarded as one of the key contributors to building positive social capital [50]. Also, it is important that policy makers, and, particularly in this case, Department of Education officers and school principals, be aware of social capital implications on adolescents’ health and life.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sports are often regarded as one of the key contributors to building positive social capital [50]. Also, it is important that policy makers, and, particularly in this case, Department of Education officers and school principals, be aware of social capital implications on adolescents’ health and life.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for negative outcomes may unActive involvement and participation in sports can intentionally serve as a platform for worsening further lead to skill development, cultural learning, intergroup relations and contribute to a divide beand overall community empowerment (Lawson, tween sportspeople, residents, and interest groups 2005; Skinner, Zakus, & Cowell, 2008). However, (Hargreaves, 2000;Ingham & McDonald, 2003;in In order to utilize sport events as vehicles and still needs to be examined.…”
mentioning
confidence: 99%
“…The potential influence of image perceptions on willingness to be involved with nonprofit sport organisations has implications for the study of concepts that are premised on social involvement, such as social capital (Skinner, et al, 2008;Spaaij, 2011). The outcomes of this study indicated that perceptions of image and legitimacy potentially led to negative connotations for sport organisations, possibly reducing individuals' willingness to become involved and thus diminishing the volume of social capital available.…”
Section: Conclusion For Theory and Practicementioning
confidence: 86%